Ethnomedicinal Knowledge of Kisan Community - A Case Study - KC, Manisha; Singh, Nanda Bahadur (Himalayan Journal of Science and Technology, 2020)
In the context of depleting indigenous knowledge and their values in the Kisan Community, they seem unaware of their culturally rich traditional practices of using animals and plants for medicinal purpose. It has been essential to document those knowledge of practices for future references. The paper tried to explore and document those knowledge and practices by the Kisan community of Mechinagar 9 and 11 of Jhapa, Nepal. For this purpose, the data were collected through interviews with key informants including conjurer (Dhami/Jhakri), elders of the society and also focal group discussions with the local people. Analysis of the data has shown that 29 animal species belonging to 24 families are used to treat 29 ailments and 57 plant species belonging to 37 families are used for treating 39 different ailments. The commonly treated ailments were common cold, cuts, wounds, diarrhoea, dysentery, etc.